Pemanfaatan Media Kolase dalam Pembelajaran Seni Rupa untuk Mengembangkan Kreativitas Siswa Kelas V SDN 1 Karangmalang - Aurelia Theysa; Nur Fajrie; Wasis Wijayanto (Jurnal Pendidikan Seni Rupa Undiksha, 2026)
Creativity is an essential aspect that needs to be developed in Arts, Culture, and Crafts (SBDP) learning at the elementary school level, particularly in visual arts education. Innovative and contextual learning approaches can help students express their ideas, imagination, and potential more optimally. One alternative medium that can be utilized is collage made from recycled waste materials, which not only enhances artistic skills but also fosters environmental awareness. This study employed a narrative qualitative approach, with data collected through observation, interviews, and documentation involving fifth-grade students of SDN 1 Karangmalang and their homeroom teacher. The collage activities used recycled snack plastic wrappers as the primary material to create artwork based on flora and fauna themes. The findings indicate that the use of collage media contributes to the development of students’ creativity, as reflected in their increased self-confidence, imagination, enthusiasm, and active participation during the learning process. Students were able to combine colors, arrange compositions, and add details according to their own ideas. The learning process was engaging and interactive, which enhanced students’ motivation in creating artwork. Therefore, recycled collage media can serve as an effective instructional strategy to create meaningful and creative learning experiences in elementary school. Keywords: Art, Collage, Creativity, Elementary School, Learning